2019
DOI: 10.2174/1381612825666190222144359
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Mineralocorticoid Receptor Antagonist Administration

Abstract: Background: Mineralocorticoid receptor antagonists consist of a class of drugs with pleiotropic beneficial effects in several cardiovascular diseases. However, physicians frequently overlook their use due to the adverse effects of such agents. Objectives: To determine the adverse effects of mineralocorticoid receptor antagonists and to suggest clinically meaningful options. We present data on the two most administered agents of this class: spironolactone and eplerenone. Method: We conducted an in-depth rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Evaluation of the transcriptional activity of those steroidal receptors demonstrated that spironolactone blocks ligand binding to human glucocorticoid receptors (GR), androgen receptors (AR), and progesterone receptors (PR) with IC 50 values of 2600, 640, and 180 nM, respectively (Table 1 ) [ 16 ]. Furthermore, spironolactone also acts as a moderate agonist for ARs and PRs, contributing to off-target side effects such as gynecomastia and irregular menstruation [ 15 ]. To compensate for those unfavorable nature of spironolactone, eplerenone was synthesized as a more selective MRB.…”
Section: Different Blocking Profiles Of Steroid Hormone Receptors By ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the transcriptional activity of those steroidal receptors demonstrated that spironolactone blocks ligand binding to human glucocorticoid receptors (GR), androgen receptors (AR), and progesterone receptors (PR) with IC 50 values of 2600, 640, and 180 nM, respectively (Table 1 ) [ 16 ]. Furthermore, spironolactone also acts as a moderate agonist for ARs and PRs, contributing to off-target side effects such as gynecomastia and irregular menstruation [ 15 ]. To compensate for those unfavorable nature of spironolactone, eplerenone was synthesized as a more selective MRB.…”
Section: Different Blocking Profiles Of Steroid Hormone Receptors By ...mentioning
confidence: 99%
“…Since the discovery in 1957 of a unique class of synthetic steroids, “spirolactones” which abolish aldosterone effects [ 9 ], several mineralocorticoid receptor blockers (MRBs) have been developed and proven to contribute to organ protection, particularly in heart failure (HF), diabetic kidney disease (DKD), and chronic kidney disease (CKD), beyond its antihypertensive effects [ 8 , 10 – 12 ]. In the current situation, spironolactone (SC-9420) and eplerenone (SC-66110, CGP-30083) are two major steroidal MRBs supported by abundant clinical evidence from many momentous trials, while those studies also elucidate limitations of those steroidal MRBs in hypertension treatment, including both renal-related and off-target side effects [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 However, due to their low selectivity, these classic MRAs may lead to serum potassium elevation, the development of gynaecomastia, female menstrual disorders, and other undesirable effects, which limits their clinical use, especially in combination with RAAS blockade. 7 In recent years, evidence has shown that the novel nonsteroidal MRA finerenone has excellent selectivity for the mineralocorticoid receptor and may have a smaller effect on serum potassium levels than classic MRAs. 8,9 However, there are no kidney outcome trials that have directly compared the efficacy of these classes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a growing amount of evidence indicates that the use of mineralocorticoid receptor antagonist (MRA) medications also contributes to slowing the progression of CKD 6 . However, due to their low selectivity, these classic MRAs may lead to serum potassium elevation, the development of gynaecomastia, female menstrual disorders, and other undesirable effects, which limits their clinical use, especially in combination with RAAS blockade 7 . In recent years, evidence has shown that the novel nonsteroidal MRA finerenone has excellent selectivity for the mineralocorticoid receptor and may have a smaller effect on serum potassium levels than classic MRAs 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Disadvantages associated with therapeutic applications of existing steroidal MRAs include the poor specificity of spironolactone for MRs, which may therefore be associated with adverse events (AEs) related to sex hormone activity, such as breast tenderness, gynecomastia, and menstrual irregularity 17 . In addition, eplerenone has weaker affinity than spironolactone for androgen and progesterone receptors but is contraindicated in diabetic patients with proteinuria and moderate or severe renal dysfunction because of an increased risk of hyperkalemia 2,18 …”
mentioning
confidence: 99%